2004
DOI: 10.2114/jpa.23.19
|View full text |Cite
|
Sign up to set email alerts
|

Calorie Restricted Diet and Urinary Pentosidine in Patients with Rheumatoid Arthritis

Abstract: Low-energy diets and fasting have suppressive effects on rheumatoid arthritis. It was reported recently that urine levels of pentosidine (i.e., an advanced glycation end product formed by glycosylation) is associated with the activity of rheumatoid arthritis. We conducted a regimen of caloric restriction combined with fasting in patients with rheumatoid arthritis, and then evaluated urinary pentosidine levels. Ten patients with rheumatoid arthritis underwent a 54-day caloric restriction program. Urinary pentos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 44 publications
0
24
0
Order By: Relevance
“…We conducted a regimen of caloric restriction combined with fasting in patients with rheumatoid arthritis, and then evaluated urinary pentosidine levels. Pentosidine was significantly decreased at the end of the study (day 54) [40]. The study showed that under a low energy diet, a reduction of disease activity in rheumatoid arthritis was accompanied by a reduction of urinary pentosidine.…”
Section: Rodriguez-garcia Et Al Measured Serum Pentosidine In Patienmentioning
confidence: 74%
“…We conducted a regimen of caloric restriction combined with fasting in patients with rheumatoid arthritis, and then evaluated urinary pentosidine levels. Pentosidine was significantly decreased at the end of the study (day 54) [40]. The study showed that under a low energy diet, a reduction of disease activity in rheumatoid arthritis was accompanied by a reduction of urinary pentosidine.…”
Section: Rodriguez-garcia Et Al Measured Serum Pentosidine In Patienmentioning
confidence: 74%
“…Our results differ from those observed in patients with rheumatoid arthritis. In the latter condition, a decrease in AGEs was observed after consecutive cycles of fasting and caloric restriction [44]; however, the entire intervention period was much longer than in our study protocol, and the primary endpoint was the urinary pentosidine level. We were only able to measure CML, a non-cross-linking type of AGEs, which may not be as strongly involved in the deterioration of cartilage integrity as is pentosidine.…”
Section: Discussionmentioning
confidence: 99%
“…There are no controlled long-term studies of reduced energy intake without mal-nutrition on patients with RA. However, Iwasahige et al [19] recently conducted a regiment for 54 days of caloric restriction combined with fasting in ten patients with RA. The patients lost in weight, and interestingly, the composite disease activity score of Lansbury was significantly reduced.…”
Section: Discussionmentioning
confidence: 99%